Microbial communication leading to the activation of silent fungal secondary metabolite gene clusters - Netzker, Tina; Fischer, Juliane; Weber, Jakob; Mattern, Derek J.; König, Claudia C.; Valiante, Vito; Schroeckh, Volker; Brakhage, Axel A. (Frontiers in Microbiology, 2015)
Microorganisms form diverse multispecies communities in various ecosystems. The high abundance of fungal and bacterial species in these consortia results in specific communication between the microorganisms. A key role in this communication is played by secondary metabolites (SMs), which are also called natural products. Recently, it was shown that interspecies ‘talk’ between microorganisms represents a physiological trigger to activate silent gene clusters leading to the formation of novel SMs by the involved species. This review focuses on mixed microbial cultivation, mainly between bacteria and fungi, with a special emphasis on the induced formation of fungal SMs in co-cultures. In addition, the role of chromatin remodeling in the induction is examined, and methodical perspectives for the analysis of natural products are presented. As an example for an intermicrobial interaction elucidated at the molecular level, we discuss the specific interaction between the filamentous fungi Aspergillus nidulans and Aspergillus fumigatus with the soil bacterium Streptomyces rapamycinicus, which provides an excellent model system to enlighten molecular concepts behind regulatory mechanisms and will pave the way to a novel avenue of drug discovery through targeted activation of silent SM gene clusters through co-cultivations of microorganisms.